Implementasi Collaborative Filtering Pada Aplikasi E-Commerce Penyewaan Costume Cosplay - Muhammad Eko Prasetyo; Andreas Nugroho Sihananto; Firza Prima Aditiawan (Jurnal Publikasi Teknik Informatika, 2024)
Cosplay, a global popular cultural phenomenon, presents a challenge for cosplayers in obtaining suitable costumes. For instance, with the surge in cosplay events in Surabaya in July 2023, the development of a costume rental application could be a solution. This application allows cosplayers to easily rent costumes, reducing the cost and effort of creating their own attire. Utilizing Collaborative Filtering and K-Nearest Neighbor (K-NN) methods, the app will recommend costumes based on user interactions within an implicit feedback system. This research aims to create a practical and cost-effective solution for cosplayers in fulfilling their costume needs for cosplay events.